1975
DOI: 10.1002/jez.1401910212
|View full text |Cite
|
Sign up to set email alerts
|

The effects of castration on song development in zebra finches (Poephila guttata)

Abstract: It has been suggested that the learning processes which occur during the critical period for bird song development are dependent on adrogens. Castration of male zebra finches (Poephila guttata, Estrildidae) at ages 9-17 days did not prevent song development, and normal learning occurred after the time of castration. Thus the learning processes of song development occur in the absence of gonadal androgens. Castrates tended to develop song more slowly than normals, which is potentially attributable to a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(121 citation statements)
references
References 17 publications
9
112
0
Order By: Relevance
“…By 1 month after the initial recording, the durations of matched sequences were shortened on average by 1.5% of their initial values, and by the final recording session the durations had shortened by 7% of their initial values. This finding is consistent with the observation of Arnold (1975) that songs of normal zebra finches can speed up after 90 d of age and indicates that there continue to be subtle changes to normal song beyond the nominal age of song "crystallization. "…”
Section: Changes To Song Temposupporting
confidence: 90%
See 1 more Smart Citation
“…By 1 month after the initial recording, the durations of matched sequences were shortened on average by 1.5% of their initial values, and by the final recording session the durations had shortened by 7% of their initial values. This finding is consistent with the observation of Arnold (1975) that songs of normal zebra finches can speed up after 90 d of age and indicates that there continue to be subtle changes to normal song beyond the nominal age of song "crystallization. "…”
Section: Changes To Song Temposupporting
confidence: 90%
“…Previous studies of the development of zebra finch song have reported that by this age individual birds have learned a fairly stable and stereotyped song ("crystallized song") that they will maintain with little modification throughout life (Immelmann, 1969;Arnold, 1975;Scharff and Nottebohm, 1991;Bottjer and Hewer, 1992;Williams and Mehta, 1999;Lombardino and Nottebohm, 2000). Our recordings from normal (control) zebra finches were generally consistent with this view.…”
Section: Control Birdssupporting
confidence: 86%
“…All males sang audible songs, whereas no female did (one produced "chattering sounds"). A second study (Arnold, 1975b), in which male zebra finches received surgery at 9 -17 days of age, found few differences between castrates and controls. Castrates did tend to develop song more slowly than control birds, but removal of the testes did not prevent the development of song learned from adult male tutors.…”
Section: Post-hatching Manipulationsmentioning
confidence: 96%
“…Zebra finch males reared in a captive colony master the imitation of adult models by the time they reach sexual maturity, 80 -90 d after hatching (Immelmann, 1969;Arnold, 1975a;Price, 1979;Böhner, 1990;Volman and Khanna, 1995). This conversion of an auditory model into a motor replica occurs only once, during the so-called "sensitive period" for song learning (but see Eales, 1985Eales, , 1987Morrison and Nottebohm, 1993).…”
mentioning
confidence: 99%